Multiwavelength Laser Module Based on Distribute Feedback Laser Diode for Broadcast and Communication Systems - P. C. Peng; K. C. Shiu; Y. M. Chen; M. A. Bitew; W. Y. Lee; C. H. Lai; Y. W. Peng (IEEE Photonics Journal)
In this paper, we proposed a cost-effective broadcast signal transmission scheme using a distributed feedback laser diode (DFB-LD) for wavelength-division-multiplexing passive optical network (WDM-PON) systems. The DFB-LD is directly modulated with a single-tone radio frequency signal to generate multiple optical carriers. An optical signal-to-noise ratio (OSNR) is enhanced using a delay interferometer as a double-pass interferometer. Orthogonal frequency division multiplexing (OFDM) and on-off keying (OOK) signals are experimentally demonstrated to test the broadcasting scheme. We measured the bit-error-rate (BER) and the power penalty after the broadcasting OFDM and OOK signals are transmitted through a 25-km single-mode fiber. An excellent performance of BER is achieved for both OOK and OFDM signals. The proposed scheme is a practical and cost-effective solution for broadcast signal transmissions in WDM-PON systems.